PENGARUH BRAND TRUST, BRAND IMAGE, PERCEIVED QUALITY, BRAND LOYALTY TERHADAP BRAND EQUITY PENGGUNA TELKOMSEL - Ayesha Rizky Nofriyanti (Ekonomi Bisnis, 2017)
Abstract : This research purpose to examine some influences among brand trust to brand equity, brand image to brand equity, perceived quality to brand equity, brand trust to brand loyalty, brand image to brand loyalty, perceived quality to brand loyalty, and brand loyalty to brand equity. The research design used descriptive and explanatory with quantitative approach. The number of samples are 75 students of master and doctoral degree Faculty of Economics and Business, Brawijaya University intake 2014, with characteristics as a Telkomsel users at least 1 year and actively recharge the amount of balance. Data collection using interview techniques and questionnaires and data processing using Partial Least Square (PLS). The result of the research shows that there is significant influence between brand trust to brand equity, brand image to brand equity, perceived quality to brand equity, brand trust to brand loyalty, brand image to brand loyalty, perceived quality to brand loyalty, and brand loyalty to brand equity. Keywords: brand equity, brand image, brand loyalty, brand trust, perceived qualityAbstrak : Penelitian ini bertujuan untuk menguji beberapa pengaruh antara lain brand trust terhadap brand equity,  brand image terhadap brand equity, perceived quality terhadap brand equity, brand trust terhadap brand loyalty, brand image terhadap brand loyalty, perceived quality terhadap brand loyalty, dan brand loyalty terhadap brand equity. Rancangan penelitian yang digunakan adalah deskriptif dan eksplanatori dengan pendekatan kuantitatif. Jumlah sampel sebesar 75 Mahasiswa S2 dan S3 Fakultas Ekonomi dan Bisnis Universitas Brawijaya angkatan 2014 sesuai dengan karakteristik populasi yaitu mahasiswa pengguna Telkomsel minimal 1 tahun dan aktif melakukan pengisian ulang. Metode pengumpulan data menggunakan teknik wawancara dan kuesioner, dengan pengolahan data menggunakan Partial Least Square (PLS).  Hasil penelitian menunjukkan adanya pengaruh signifikan antara variabel brand trust terhadap brand equity, brand image terhadap brand equity, perceived quality terhadap brand equity, brand trust terhadap brand loyalty, brand image terhadap brand loyalty, perceived quality terhadap brand loyalty, serta brand loyalty terhadap brand equity.Kata kunci: brand equity, brand image, brand loyalty, brand trust, perceived quality